2017
DOI: 10.15277/bjd.2017.137
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and impact of implementing NICE guidance on diabetes control during delivery

Abstract: Aims: The aim of this study was to report on the practicality, feasibility and impact of implementing the National Institute for Health and Care Excellence (NICE) guidelines for the control of diabetes in women during labour and birth. Methods: We analysed case records of pregnant women with diabetes who delivered in the period between July 2014 and June 2015. The data were collected in relation to the availability of a plan in the notes, capillary blood glucose (CBG) monitoring, use of variable rate intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Dashora et al [6] found that the incidence of hypoglycaemia was 22% in women on variable-rate i.v. insulin infusion to achieve an intrapartum target of 4-7 mmol/l [6]. Moreover, in that study, only 45% of women had hourly capillary blood glucose monitoring.…”
Section: Pseudoaxioms In the Intrapartum Management Of Diabetesmentioning
confidence: 99%
“…Dashora et al [6] found that the incidence of hypoglycaemia was 22% in women on variable-rate i.v. insulin infusion to achieve an intrapartum target of 4-7 mmol/l [6]. Moreover, in that study, only 45% of women had hourly capillary blood glucose monitoring.…”
Section: Pseudoaxioms In the Intrapartum Management Of Diabetesmentioning
confidence: 99%
“…dextrose continues to be as high as 28% in a recent multicentre randomized controlled trial setting [13]. Based on capillary glucose levels, 47% neonates had a glucose measurement < 2.6 mmol/l in another study [14].…”
Section: Glycaemic Control During Labour and Deliverymentioning
confidence: 99%
“…However, Kline and Edwards [6] also report a neonatal hypoglycaemia rate of 69%, and the majority of maternal episodes were asymptomatic and discovered incidentally because of the monitoring protocol. Thus, maternal hypoglycaemia during variable rate intravenous insulin infusion has never been a major issue in practice because women are under close supervision with hourly monitoring and are easily treated [9]. Thus, maternal hypoglycaemia during variable rate intravenous insulin infusion has never been a major issue in practice because women are under close supervision with hourly monitoring and are easily treated [9].…”
Section: Accepted 3 September 2018mentioning
confidence: 99%
“…Others have reported zero maternal hypoglycaemia [7] and 7 of 23 studies in a recent metaanalysis did not report any maternal hypoglycaemia [8]. Thus, maternal hypoglycaemia during variable rate intravenous insulin infusion has never been a major issue in practice because women are under close supervision with hourly monitoring and are easily treated [9]. A review of 24 published papers of various protocols for glycaemic control in women with diabetes during labour demonstrated that a target capillary blood glucose of 4.0-6.0 mmol/l can be used safely with a low rate of neonatal hypoglycaemia [10].…”
mentioning
confidence: 99%